The UK ECAD Initiative 1986-1991, an appraisal - Jones, Peter L. (Zielona Góra: Uniwersytet Zielonogórski)
The various aspects of establishing and running the ECAD Initiative are described. Each activity is examined critically and the changes that proved necessary as the scheme developed are charted from the scheme's inception in 1986 to the present day.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka